Privacy-Preserving Healthcare Analytics in Indonesia Using Lightweight Blockchain and Federated Learning: Current Landscape and Open Challenges - Mardiansyah, Viddi; Bayuaji, Luhur; Herlistiono, Iwa Ovyawan; Violina, Sriyani; Purnama, Adi; Prasetyo, Bagus Alit; Huynh, Phuoc-Hai (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Healthcare data are invaluable assets in today’s digital age; however, they are also highly vulnerable to misuse, breaches, and unauthorized access. The global healthcare sector faces a significant dilemma: To leverage exceptionally enormous and heterogeneous datasets, the protection of patient privacy must be ensured while simultaneously improving medical services and public health understanding. In recent years, blockchain technology has emerged as a promising solution to manage healthcare data in a decentralized, transparent, tamperproof, as well as secure way. However, several natural limitations often obstruct many conventional blockchain systems. These limitations include scalability issues, high energy consumption, in addition to increased latency, and they can greatly impede practical adoption in resource-limited settings, particularly in developing countries such as Indonesia. These many limitations considerably spurred developers to create lightweight blockchain frameworks. These frameworks aim to retain all of the core benefits of blockchain, such as its immutability in addition to traceability, and optimize both performance and efficiency. In the event that an individual integrates the proposed system by means of federated learning, which allows training of machine learning models across distributed data sources without data privacy being compromised, the system subsequently offers a compelling solution for healthcare analytics that preserves privacy in its entirety. This paper explores integrated technologies in Indonesian healthcare and highlights their potential and limitations. This study discusses how data can improve services while protecting patient confidentiality despite increasing cyber threats. It also considers regional policies like the Personal Data Protection Law and the BPJS health insurance. Identified are certain open challenges, in addition to particular future research directions, for the purpose of addressing the practical, technical, and regulatory hurdles that must be overcome to realize secure and privacy-aware healthcare analytics in Indonesia.